Evaluation of Contralateral Limb Cross Education and High-Frequency Repetitive Transcranial Magnetic Stimulation on Functional Indices of the Affected Upper Limb in Subacute Phase of Stroke - Katayoon Rezaei; Amin Kordi Yoosefinejad; Farzaneh Moslemi Haghighi; Mohsen Razeghi (Stroke Research and Treatment)
Background. Stroke is one of the causes of long-term morbidity. Despite rehabilitation strategies, most survivors live with motor deficits in the upper limbs. Objectives. The aim of the study was to compare the effect of contralateral cross education (CE) and high-frequency repetitive magnetic stimulation (HF-rTMS) on the function of upper extremity in subacute phase of stroke. Methods. Forty patients were randomly assigned into 4 groups. Group “A” received physical therapy (PT) for 10 sessions, 3 times per week. Group “B” received PT and HF-rTMS as follows: stimulation of 20 Hz for 5 s, intertrain interval for 50 s, 20 trains, 2000 pulses at 90% resting motor threshold, and conventional PT. Group “C” was treated with CE and PT. In group “D,” HF-rTMS, CE, and PT were administered. Results. Significant differences were found in the Fugl-Meyer scale between “A” and “C” (P=0.01), “A” and “D” (P=0.02), and “B” and “C” groups (P=0.01). In the box-block test, there were significant differences between “A” and “B” (P=0.01), “A” and “C” (P<0.001), “B” and “D” (P=0.001), and “B” and “C” groups (P=0.01). Statistical differences were observed in grip strength between “A” and “B” (P=0.01) and “A” and “C” groups (P=0.02). Conclusions. It is suggested that clinicians select the therapeutic methods in line with their expected goal. When the goal is to improve upper extremity function, CE+PT could be more effective than HF-rTMS+PT. Also, CE+PT and HF-rTMS+PT were more effective than CE+HF-rTMS+PT at improving grip strength. Therefore, combining several methods would not always lead to better results.